House prices and Islamic bank stability in Indonesia : evidence from autoregressive distributed lag (ARDL) model - Sukmana, Raditya; Setianto, Rahmat Heru (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examines the effect of house prices on Islamic bank stability in the long run and their short run dynamic interactions with real output and interest rate for the case of Indonesia. As bank risks may response differently to the shock of house prices, the aggregate and disaggregate house price indices, namely, small house price indices, medium house price indices and large house price indices, are applied in the analysis. By employing autoregressive distribution lag (ARDL) test for co-integration, we find the presence of long run relationship between house prices, Islamic bank risk and macroeconomic variables. A long run relationship is also found for the medium and large-house prices’ indices. The estimated long run coefficient is found to be supportive to the deviation hypothesis. Furthermore, results from the impulse response functions (IRFs) and error correction mechanism (ECM) reflect the short run dynamic interactions between house prices and bank credit. The results from disaggregate analysis reveal that only small-house prices have the relationship with Islamic bank risk, and interestingly, the results support the deviations hypothesis. Our findings have important implications for bankers, monetary authority and investors in determining policy and business decisions especially in stabilizing house price for low income earners.